A Bibliometric Review of Research on Leadership onWork Satisfaction - Widyastuti, Pratiwi; Wahyuningsih, Sri Handari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper aims to identify research trends in leadership performance on work satisfaction from 2018-2023 indexed by Scopus.The Method used in this study is qualitative research with a literature study approach. As for the data found, 21 documents were obtained and analyzed 2018-2023. This dataset was converted to CSV format andfor Bibliometrix in the analysis using VOSviwer.This research showed that the trend from 2018 to 2023 indexed by Scopus has decreased. This decline may be due to many things, such as researchers' interests, changing research viewpoints, or new issues receiving greater attention. Furthermore, the visualization mapping shows that Leadership, Job Satisfaction, Work Satisfaction, Employee Performance, and Motivation are the main focus of Leadership and Work Satisfaction research.The paper also provides an alternative approach to conducting a literature review with a computer-aided analysis program.